Robot-assisted percutaneous screw fixation in the treatment of navicular fracture - Wang, Cheng; Fu, Shaoling; Li, Xueqian; Wang, Jiazheng; Wu, Chenglin; Zhang, Jieyuan; Song, Guoxun; Gu, Wenqi; Shi, Zhongmin (Frontiers in Surgery, 2023)
Background Long recovery time, large scar, postoperative swelling and pain are possible side effects of open reduction internal fixation (ORIF) for tarsal navicular fractures. Early exercise instruction is made possible by the use of an intraoperative robot-assisted percutaneous invasive closed reduction internal fixation. The goal of the trial was to determine whether percutaneous screw internal fixation with robot assistance might be used to treat navicular fractures. Methods 27 patients with navicular fractures had surgical treatment between June 2019 and December 2021. Of those, 20 instances were treated with ORIF, while 7 cases had robot-assisted percutaneous screw internal fixation. At the final follow-up, the American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot score and the visual analogue scale (VAS) score were compared to determine outcomes and function. Results Follow-up was obtained in all 27 patients after surgery, with a mean follow-up time of 21.81 months, ranging from 15 to 29 months . In the 7 instances of robot-assisted group, percutaneous guide wire insertion and screw placement only needed one attempt and the depth and position of the implant were both satisfactory. In the ORIF group, there were two patients who sustained cutaneous nerve injuries. The AOFAS score and the VAS score of the group receiving robot-assisted navigation percutaneous screw fixation were 92.25 ± 2.22 and 0.75 ± 0.25 respectively at the last follow-up, while 82.25 ± 7.15 and 0.50 ± 0.29 were the respective values for the ORIF group. Conclusion Intraoperative robot-assisted percutaneous closed reduction internal fixation for tarsal navicular fractures can accomplish exact localization of fracture site, reduce soft tissue damage and operative time. According to current view, this method offers fewer complications, a faster recovery after surgery, and more patient satisfaction.